Measurement of the Milky Way's Rotation Curve using BURT Radio Observations at the 21 cm Line of Neutral Hydrogen - Hussein, Z. A.; Mahdi, H. S. (Iraqi Journal of Science, 2025)
With a small radio telescope in a high-noise area, this paper measured the Milky Way's rotation curve using the Tangent Point Method, by the Baghdad University Radio Telescope (BURT). It is placed on the Department of Astronomy and Space roof, and observes a 21-cm HI emission line, scanning the galaxy's first quadrant systematically. From 0° to 90° galactic longitude, by increasing 5°, the telescope identifies the highest recession velocity, corresponding to clouds orbiting tangent to the line of observation. The rotation curve, plotting galactic rotational velocity against distance from the centre, is anticipated to be flat, indicative of uniform mass distribution. However, observed deviations challenge this expectation, revealing non-flat curves and prompting the exploration of the dark matter problem. Anomalies in the rotation curve imply unseen mass in the galaxy, expanding our comprehension of the Milky Way's composition and contributing crucial insights into the pervasive mystery of dark matter.